2023
DOI: 10.3389/fdgth.2022.1086652
|View full text |Cite
|
Sign up to set email alerts
|

Designing for patient decision-making: Design challenges generated by patients with atrial fibrillation during evaluation of a decision aid prototype

Abstract: Shared decision-making (SDM) empowers patients and care teams to determine the best treatment plan in alignment with the patient's preferences and goals. Decision aids are proven tools to support high quality SDM. Patients with atrial fibrillation (AF), the most common cardiac arrhythmia, struggle to identify optimal rhythm and symptom management strategies and could benefit from a decision aid. In this Brief Research Report, we describe the development and preliminary evaluation of an interactive decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In particular, they expressed a need for structured, personalized information (45). Related work shows that the need for evidence and personalized, credible information is also present in cardiac patients (23,46). Sankaran et al (41) demonstrated how a single DHT can address these needs.…”
Section: Providing Patient Information and Hcp Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they expressed a need for structured, personalized information (45). Related work shows that the need for evidence and personalized, credible information is also present in cardiac patients (23,46). Sankaran et al (41) demonstrated how a single DHT can address these needs.…”
Section: Providing Patient Information and Hcp Educationmentioning
confidence: 99%
“…Patients are wellinformed about their options and able to actively participate in selecting treatment plans that align with their goals and values. The premise of practical use is that DHTs provide personal content tailored to individual factors, such as gender, age, level of knowledge, and diagnosis (23,46). Interventions should also respect patients' preferences regarding their degree of involvement in SDM and tailor the support accordingly.…”
Section: Aim Recommendationsmentioning
confidence: 99%